Impulsivity in borderline personality disorder. Issue 9 (20th January 2015) - Barker, V.; Romaniuk, L.; Cardinal, R. N.; Pope, M.; Nicol, K.; Hall, J.
Abstract : Background: Impulsivity is a core feature of borderline personality disorder (BPD) and is most frequently measured using self-rating scales. There is a need to find objective, valid and reliable measures of impulsivity. This study aimed to examine performance of participants with BPD compared with healthy controls on delay and probabilistic discounting tasks and the stop-signal task (SST), which are objective measures of choice and motor impulsivity, respectively. Method: A total of 20 participants with BPD and 21 healthy control participants completed delay and probabilistic discounting tasks and the SST. They also completed the Barratt Impulsiveness Scale (BIS), a self-rating measure of impulsivity. Results: Participants with BPD showed significantly greater delay discounting than controls, manifest as a greater tendency to accept the immediately available lesser reward rather than waiting longer for a greater reward. Similarly they showed significantly greater discounting of rewards by the probability of payout, which correlated with past childhood trauma. Participants with BPD were found to choose the more certain and/or immediate rewards, irrespective of the value. On the SST the BPD and control groups did not differ significantly, demonstrating no difference in motor impulsivity. There was no significant difference between groups on self-reported impulsivity as measured by the BIS. Conclusions: Measures of impulsivity show that while motor impulsivity was not significantly different in participants with BPD compared with controls, choice or reward-related impulsivity was significantly affected in those with BPD. This suggests that choice impulsivity but not motor impulsivity is a core feature of BPD.